High mutation prevalence of precore and basal core promoter in pregnant women who underwent spontaneous HBeAg seroconversion within one year postpartum - Luo, Yuqian; Pan, Mingjie; Ning, Mingzhe; Chenyu, Xu; Liu, Lanhua; Chen, Liping; Chen, Tingmei; Biyun, Xu; Yali, Hu; Zhou, Yi-Hua (Digestive and liver disease, 2020)
Seroconversion of hepatitis B e antigen (HBeAg) is a critical event in the natural course of hepatitis B virus (HBV) infection. We herein characterize the virological factors associated with postpartum spontaneous HBeAg seroconversion. A total of 214 pregnant women positive for both hepatitis B surface antigen (HBsAg) and HBeAg were followed up at 7–12 months postpartum. Of the subjects, 26 (12.1%) achieved spontaneous HBeAg seroconversion. Receiver operating curve analysis indicated that HBV DNA level <1.0 × 107 IU/mL, HBsAg <1.0 × 104 IU/mL and HBeAg <7.36 × 102 S/CO each independently predicted HBeAg seroconversion within 12 months postpartum. At delivery, 73.1% (19/26) women with postpartum HBeAg seroconversion had precore (PC) and/or basal core promoter (BCP) mutations, higher than that (5/36, 13.9%) in the women without postpartum seroconversion. Binary logistic regression analysis indicated that the presence of mutations in PC, BCP, and both PC and BCP at delivery was associated with an increased likelihood (OR = 13.286, 16. 238, and 22.143 respectively, all P < 0.05) to undergo postpartum spontaneous HBeAg seroconversion. These results suggest that quantitative determination of virological markers and sequencing PC and BCP can predict spontaneous HBeAg seroconversion, which could be valuable in deciding antiviral therapy against HBV.